Effect of disintegrates and metabolites of Lactobacillus rhamnosus and Saccharomyces boulardii on biofilms of antibiotic resistant conditionally pathogenic and pathogenic bacteria - O. Y. Isayenko; O. V. Knysh; Y. M. Babych; T. N. Ryzhkova; G. I. Dyukareva (Regulatory Mechanisms in Biosystems, 2019)
The work presented here is the first to examine the impact of Lactobacillus rhamnosus GG ATCC 53103 and Saccharomyces boulardii metabolites obtained using the author`s method on the formation of biofilm forms of bacteria. The structural components of the probiotic microorganisms were obtained using the method of physical disintegration – low frequency ultrasound waves produced by a G3-109 generator. Metabolites were obtained by cultivating L. rhamnosus and S. boulardii in ultrasound disintegrates of lactobacteria and Saccharomycetes. The impact of biologically active substances on the formation of biofilm of Corynebacterium ulcerans tox+ 112, C. diphtheriae gravis tox+ 108, by antibiotic-resistant Pseudomonas aeruginosa PR, Klebsiella pneumoniae PR, Lelliottia amnigena (Enterobacter amnigenus) PR and P. aeruginosa AТСС 27853 reference strain was studied using the spectrophotometric method. For the first time, we proved that L. rhamnosus GG and S. boulardii metabolites and combinations of metabolites of Saccharomycetes and lactobacteria, obtained by cultivating primary producers in their disintegrates, damage preformed 24-hour biofilms of gram-positive and gram-negative bacteria. The representatives of Corynebacterium exhibited higher sensitivity to the filtrates of disintegrates and products of vital activity of lactobacteria and Saccharomycetes than gram-negative pathogens. High parameters of decrease in optical density of preformed biofilms of Corynebacterium and antibiotic-resistant gram-negative bacteria were observed under the influence of combination of L. rhamnosus GG and S. boulardii metabolites (by 1.3–2.6 times). However, the largest reduction of the optical density of the formed biofilm of all studied strains was observed under the influence of metabolites of lactobacteria (by 1.5–5.3 times). Biologically active substances of L. rhamnosus GG and S. boulardii obtained using the author’s method can be used as candidate preparations which could have a strong influence on the process of the formation of the biofilms and preformed biofilms, and also as a preparations of substitution/addition of therapeutic prescription.